Bioactive Herbal Extracts of Traditional Chinese Medicine Applied with the Biomaterials: For the Current Applications and Advances in the Musculoskeletal System - Li, Haotao; Wu, Rongjie; Yu, Haiyang; Zheng, Qiujian; Chen, Yuanfeng (Frontiers in Pharmacology, 2021)
Traditional Chinese medicine (TCM) has demonstrated superior therapeutic effect for musculoskeletal diseases for thousands years. Recently, the herbal extraction of TCM has received rapid advances in musculoskeletal tissue engineering (MTE). A literature review collecting both English and Chinese references on bioactive herbal extractions of TCM in biomaterial-based approaches was performed. This review provides an up-to-date overview of application of TCMs in the field of MTE, involving regulation of multiple signaling pathways in osteogenesis, angiogenesis, anti-osteoclastogenesis, anti-inflammation and chondrogenesis. Meanwhile, we highlight the potential advantages of TCM, opening the possibility of its extensive application in MTE. Overall, the superiority of traditional Chinese medicine turns it into an attractive candidate for coupling with advanced additive manufacturing technology.